2014
DOI: 10.1021/ol5028706
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)-Catalyzed Polycyclization of Linear Dienediynes to Seven-Membered Ring-Containing Polycycles via Tandem Cyclopropanation/Cope Rearrangement/C–H Activation

Abstract: The presented step‐economic synthesis of complex molecules proceeds with moderate to excellent diastereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 53 publications
(18 reference statements)
1
25
0
Order By: Relevance
“…In 2014, Yu's group (Cai et al, 2014) reported a cascade cyclization for polycyclic carbocycles via gold(I)-catalyzed sequential cyclopropanation, cope rearrangement, and C-H functionalization of linear dienediyne substrates. A 6/7/5-fused tricyclic skeleton can be obtained, which exists in some natural diterpenes such as daphnane and tigliane families ( Figure 1C).…”
Section: Construction Of Polycyclic Carbocyclesmentioning
confidence: 99%
“…In 2014, Yu's group (Cai et al, 2014) reported a cascade cyclization for polycyclic carbocycles via gold(I)-catalyzed sequential cyclopropanation, cope rearrangement, and C-H functionalization of linear dienediyne substrates. A 6/7/5-fused tricyclic skeleton can be obtained, which exists in some natural diterpenes such as daphnane and tigliane families ( Figure 1C).…”
Section: Construction Of Polycyclic Carbocyclesmentioning
confidence: 99%
“…Yu and coworkers designed a new gold-catalyzed reaction for the synthesis of 5,7,6-tricyclic ring systems by the polycyclization of linear dienediynes 154 with high diastereocontrol in one step (Scheme 37). [36] There is another chance of creating a different tricyclic compound by the deprotonation followed by prodeauration of carbocation intermediate and regenerate the gold catalyst. They have applied this strategy to a wide variety of substrates in the presence of 10 mol% of gold catalyst 155 in DCE at room temperature affording good to excellent yields of the products.…”
Section: Gold-catalyzed Coupling Reactions Through Csp 2 à H Bond Actmentioning
confidence: 99%
“…Proposed reaction mechanism for the gold-catalyzed synthesis of seven membered ring containing polycycles via tandem polycyclization. Adapted from ref 36. with permission.…”
mentioning
confidence: 99%
“…The reaction sequence on 73 followed a Cope rearrangement, formation of a strained seven‐membered‐cyclic allene ( 74 ), and an aliphatic C−H activation triggering 1,2‐H (or OAc) shifts. The long cascade reaction sequence efficiently built up fused 5,7,6‐tricyclic ring systems ( 77 ) in one step and with a high diastereoselectivity …”
Section: Synthesis Of Bio‐relevant Small To Medium Ring‐heterocyclesmentioning
confidence: 99%